Legal Supply of Parliamentary Opposition Activities In the English-American and Roman-German Legal Systems: Comparative Analysis - Hrubinko, Andrii; Kucher, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The peculiarities legal support of the functioning parliamentary opposition in the countries of Anglo-American and Romano-German legal systems are investigated. In the study of the problem, comparative analysis as the main method are used. The characteristic features of the organization of parliamentary opposition in a number of foreign countries have been identified and investigated.According to the results of the study it is concluded that the experience of foreign countries should be embodied in domestic practice, provided that the appropriate institution of opposition is included in the legal field (legislation) of Ukraine. The most advanced models for the effective operation and protection of opposition rights are the German and Westminster models of parliamentary opposition.The institutionalization of the opposition in democratic systems should not contradict the basic principle of separation of powers, and therefore it deliberately proceeds from the recognition of the limited sphere of influence of the opposition, which is localized in parliament and operates by parliamentary methods. The desire for alternative government does not allow for significant influence of the parliamentary opposition on the formulation and implementation of government policy, but does not limit the influence of the opposition as a political force on the electoral field. Democratic legislation establishes or may set framework conditions for parliamentary opposition activity.